Why ESSA has been reform without repair. (October 2019) - Saultz, Andrew; Schneider, Jack; McGovern, Karalyn
The Every Student Succeeds Act (ESSA) was designed to remedy the wrongs of No Child Left Behind (NCLB). Yet Andrew Saultz, Jack Schneider, and Karalyn McGovern explain that, so far, it has failed to fundamentally alter how the federal government interacts with schools. They discuss the need for federal authority over issues of equity in education and how federal authority has expanded over time, leading to the accountability movement, which, under NCLB, required schools to provide quantifiable measures of student achievement. Although ESSA was touted as a return of control to the states, states are still held accountable for testing requirements, reporting data, and sanctioning underperformance. The authors recommend instead a model of rigid flexibility, in which centralized offices might require certain activities but allow schools some choice in determining specific goals .